ASSESSMENT OF THE IMPACT OF TECHNOLOGIES FOR GROWING PERENNIAL GRASSES AND PERENNIAL PLANTATIONS USING ORGANIC TECHNOLOGY ON THE ORGANIC CARBON CONTENT AND BIOLOGICAL ACTIVITY OF DARK GRAY PODZOLIZED SOIL - Ласло, Оксана; Марініч, Любов (SWorldJournal, 2025)
The article highlights research based on a comparison of the organic carbon content and assessment of the biological activity of dark gray podzolized soil depending on the cultivation of perennial grasses and perennial plantations using organic technology